(untitled) (Research, Society and Development, 2023)
Breast cancer is the second most common type of cancer among women and the deadliest in the world. Estimates point to a significant increase in new cases of this type of cancer in recent years, which characterizes a thematic theme such as the problem of public health. The objective of the study is to understand the impacts and family dynamics of women in the treatment of breast cancer. The results indicate that the diagnosis and treatment impact on several dimensions of a woman’s life, including a family member. The illness by cancer affects the whole family, which is an interconnected system, in which one exercise influences the others. Among these impacts, there is also the fear of losing this woman to the disease, the changes in social roles are highlighted, emotions such as anxiety, feelings of impotence, anger, sadness, stress and demands on the part of companions are also perceived. . Deepen public knowledge, so that it is possible to develop relevant strategic strategies, since it is necessary for this knowledge to be relevant, since this performance of the hospital psychologist is once necessary.